THE STRUGGLE OF TEACHERS AGAINST NEOLIBERAL REFORMS IN BRAZIL AND FRANCE - Paula, Ricardo Pires de [UNESP]; Robert, Andre D. (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
The present text aims to give an overview of the teachers' union struggle against neoliberal reforms based on the comparison between Brazil and France. With this, we elected two unions, APEOESP (Union of Teachers of the Official Teaching of the State of Sao Paulo) in Brazil and SNES (Syndicat National des Enseignements de Second Degree) in France. This choice occurs because of the importance of both in the campaign against neoliberal policies in their respective countries during the 1990s and 2000s. As neoliberal policies branch out in quite broad areas, we have decided to emphasize those that affect all workers, social security reform. We chose to analyze the performance of the teachers' unions around the counter- reforms of the social security system in 2003 in France and Brazil. We used as main source of the research presented here the periodicals Jornal da Apeoesp and L'Universite Syndicaliste (L'US), APEOESP and SNES, respectively.
Keywords: neoliberalism; counter-reform of social security; APEOESP; SNES